Oracle PL/SQL Programming - Feuerstein(3, (BStevens; Priby(3, (BBills (New york O,Reilly Media, 2009)
Including the edition based redefinition capability function result cache continue statement compound triggers and securefiles oracle is committed to pl/sql as the language of choice for implementing business logic in the database
12
Keywords: Computer Software; Databas management -- Computer software